Characterization of pentocin TV35b, a broad-spectrum antimicrobial peptide produced by Lactobacillus pentosus isolated from the human vagina - Okkers, D. J.(Deidre Janine),1974- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1999.